Seasonal Variations of Milk Composition of Sarda and Saanen Dairy Goats - Paola Scano; Pierluigi Caboni (Dairy, 2022)
Traditionally, in Mediterranean areas the goat population was composed of autochthonous breeds with strong milk production seasonality. In the last decades, high productive alpine breeds were introduced together with more widespread out-of-season milk production practices. This study is a large-scale survey on the seasonal variations of the main compositional characteristics of goat milk obtained from Sarda and Saanen breeds reared on the Mediterranean island of Sardinia (Italy). Analysis of data indicated that milk from the Sarda breed was significantly richer, at p < 0.001, in protein, fat, and lactose, and had a lower urea mean content than Saanen. Throughout the year, fluctuations of mean contents of the milk parameters were similar for the two groups of goats, indicating that, besides genetic intrinsic differences, climate and herbage growth influenced the Sarda as well as the Saanen goats. During the summer, milk from Saanen showed a marked drop in fat and protein contents, with 21% of samples showing a fat-to-protein ratio <1. No significant differences were found for the somatic cell count; however, the Sarda breed showed a higher bacterial count, suggesting improper milk handling and/or storage equipment more frequently encountered in extensive and semi-extensive farm systems.